From Ford to the Olympics - Egidio Dansero; Matteo Puttilli (Revue de Géographie Alpine)
In 2006, Sestriere played a leading role in the organization of the Torino Winter Olympic Games. The event was crucial to rethinking the city’s development model, which, since its foundation in 1934, hinged on two specific vocations: winter sports tourism and the close link with Torino, where the Agnelli family, the major force behind Sestriere’s foundation, had operated the FIAT auto factories since the Twenties. Because of these characteristics, Sestriere has long been an archetypal model of a ski resort, though it has received surprisingly little attention in the literature. In view of the deep-seated crisis that has made it necessary to move away from the traditional ski resort model, the paper uses a territorial perspective to investigate how Sestriere has evolved in response to the major periods of change in Alpine tourism. Our hypothesis is that the resort is at the center of a dense network of multi-scalar territorial relationships (with the city, with the surrounding towns, and with the major international flows), which at the same time provide a means of interpreting and analyzing the resort’s territoriality and a fundamental resource to be leveraged in rejuvenating its development models.